Barriers to telemedicine adoption among rural communities in developing countries: A systematic review and proposed framework - Haifa Mayang Lestari; Adriana Viola Miranda; Ahmad Fuady (Elsevier, 2024)
Objective: Telemedicine has the potential to improve healthcare access in rural areas, 56 % of which do not have access to essential healthcare services. However, systemic barriers continue to limit its adoption. This systematic review aimed to identify the current barriers to telemedicine adoption in the rural areas of developing countries. Data sources: A systematic literature search using six databases (PubMed, Cochrane, Proquest, Scopus, SpringerLink, and EBSCO) was performed to identify articles on barriers to telemedicine adoption published until May 2024. Additional studies were included through hand searching and reference list checking. Study selection: Study selection was done independently by two reviewers using pre-specified inclusion and exclusion criteria. Data extraction: Critical appraisal was conducted using the AXIS tool for cross-sectional studies, the Consolidated Criteria for Reporting Qualitative Studies (COREQ) checklist for qualitative studies, and the Mixed-Methods Appraisal Tool (MMAT) for mixed-methods studies. Data synthesis: The reporting of this article follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement. We included 21 studies (eight cross-sectional studies, eleven qualitative studies, and two mixed-methods studies) from twelve Asian, African, and South American countries. We classified the identified barriers into the five domains of a novel '5P framework': product, provider, public, place, and policy. Each of these domains is essential for telemedicine adoption and its sustainability. Conclusion: It is crucial to understand the context of the rural areas targeted for telemedicine adoption. Addressing the barriers identified through the '5P framework' by conducting culturally sensitive and context-specific efforts may pave the way to the maximization of telemedicine adoption in rural areas.